2020
DOI: 10.22582/ta.v8i2.529
|View full text |Cite
|
Sign up to set email alerts
|

Teaching Anthropology With Museum Collections

Abstract: Material culture provides powerful teaching opportunities for core anthropological themes and issues. Based on experience in teaching both undergraduate and postgraduate students, teh authors provide examples and a framework for a class exercise which supports students to learn from objects and to think anthropologically about them.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2
1

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(3 citation statements)
references
References 8 publications
0
3
0
Order By: Relevance
“…Furthermore, first-hand experience and the ability to make autonomous decisions about the fields enabled students to reflect on course topics, generating a direct and personal dialogue with the people and objects in the field (Ortner 1995). This assumption is even more relevant in the context of studying material culture and museum experiences, as direct contact with objects can foster deeper learning and critical skills (Peers and Vitelli 2020). At the same time, dialogue with the Kamayurá delegates provided students an opportunity to explore a new ethic of exhibition practices and the appropriation of museum spaces by different agents (Kreps 2015).…”
Section: Some Notes On the Anthropology And Museums Course Experiencementioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, first-hand experience and the ability to make autonomous decisions about the fields enabled students to reflect on course topics, generating a direct and personal dialogue with the people and objects in the field (Ortner 1995). This assumption is even more relevant in the context of studying material culture and museum experiences, as direct contact with objects can foster deeper learning and critical skills (Peers and Vitelli 2020). At the same time, dialogue with the Kamayurá delegates provided students an opportunity to explore a new ethic of exhibition practices and the appropriation of museum spaces by different agents (Kreps 2015).…”
Section: Some Notes On the Anthropology And Museums Course Experiencementioning
confidence: 99%
“…There has been a growing global interest in incorporating material culture studies into teaching programs (e.g., Chatterjee and Hannan 2015;Dias 2013;Nichols 2019;Peers and Vitelli 2020;Woodward 2016). Several authors emphasize how interaction with material culture provides both direct sensory experiences (Edwards et al 2006) and mental engagements with the world (Malafouris 2013).…”
Section: Introductionmentioning
confidence: 99%
“…The analysis of cataloging activities in PCTO plans showed that laboratory work using school museum collections improves students' observational and reasoning skills. They also represent valuable tools for enhancing scientific literacy [180] and developing interdisciplinary proposals even in traditional classroom lessons. The case study discussed in this study showed that, when recovered and made newly accessible to teachers and students, natural history school collections become valuable tools for transdisciplinary practical learning.…”
Section: Discussionmentioning
confidence: 99%